Exploring Gender Differences In Science Engagement and Achievement: A Metaanalytic Approach - Nabilla Salma; Zakia Fariza Umami (International Journal of Mathematics and Science Education, 2024)
This metaanalysis examines gender differences in science engagement and achievement across primary and secondary education levels. By synthesizing data from over 50 studies conducted in various educational settings, the research identifies patterns in attitudes, performance, and engagement between male and female students. The analysis reveals that gender disparities in science achievement are minimal; however, engagement and interest levels show significant variances, with implications for educational strategies aimed at fostering equal engagement in science.